Meta-Analysis of failure of prehospital endotracheal intubation in pediatric patients (2020)
Prehospital care is essential for airway preservation in pediatric patients who require early endotracheal intubation to improve oxygenation and prevent aspiration. However, high frequencies of failure of endotracheal intubation have been reported for this age group. We aimed to analyze the frequency of failure of endotracheal intubation in pediatric patients within a prehospital context and compare it with adult patients. Thus, a systematic revision of literature with a meta-analysis was performed using a study search and selection strategy ensuring extensiveness, sensitivity, and reproducibility. Meta-analyses were performed for odds ratio, DerSimonian and Laird’s Q test was used to assess heterogeneity, and Egger and Begg’s test was used to assess publication bias. Overall, 17 papers and 8772 patients were included, and the main cause of prehospital care was assessed to be trauma. Failed endotracheal intubation frequency was 0.4%–52.6% in pediatric patients. The most frequent complication was with esophageal intubation. Forest plot suggests that risk of failure during intubation of pediatric patients is 3.54 fold higher than that observed for adults. It was concluded that airway management in pediatric patients within a prehospital context is a challenge for prehospital care providers because it entails clear physiological and anatomical differences and a low frequency of exposure to this kind of events as opposed to adults. These differences support a widely higher risk of failure of intubation, suggesting the necessity of consistently trained prehospital care providers to ensure proficiency in technique as well as availability of the required equipment.